Gaya Bahasa di Lirik Lagu Tulus dalam Album Manusia (Sebuah Kajian Semantik) - Nora, Risma (J-LELC: Journal of Language Education, Linguistics, and Culture, 2022)
This research is entitled Language Style in Tulus Song Lyrics in Human Album. This study aims to 1) describe the use of language styles contained in the collection of Tulus song lyrics. This study used descriptive qualitative method. Data was collected by using the note-taking method. The data in this study are in the form of song lyrics containing the dominant language style of hyperbole. Sources of data used in this study are 10 song lyrics in the album Tulus. Based on the results of the analysis, 16 data were found that used language styles. The use of this language style gives rise to meaning that makes a song can be enjoyed beautifully.